2001
DOI: 10.1055/s-2001-18339
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAnti-Inflammatory Effects of Quercetin 3-O-Methyl Ether and Other Constituents fromRhamnusSpecies

Abstract: The anti-inflammatory activities of the isolated flavonoids, quercetin 3-O-methyl ether (1), kaempferol (2), and quercetin (3), of Rhamnus nakaharai, and anthraquinone, frangulin B (4), of Rhamnus formosana, were assessed in vitro by determining their inhibitory effects on the chemical mediators released from mast cells, neutrophils, macrophages, and microglial cells. Compounds 1 - 3 strongly inhibited the release of beta-glucuronidase and lysozyme from rat neutrophils stimulated with formyl-Met-Leu-Phe/cytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 1 publication
1
29
0
1
Order By: Relevance
“…Through bioassay-guided fractionation procedures three flavonoids, 3-O-methylquercetin (1), 3,7-O-dimethylquercetin (2) and 3,7-O-dimethylkaempferol (3), were isolated as the potent antinociceptive and anti-inflammatory principles. Although 1 was previously reported to possess in vivo anti-inflammatory activity (Wei et al, 2001), this is the first report on the in vivo antiinflammatory and antinociceptive effects of other flavonoids 2 and 3. A remarkable point might be the potency of these flavonoids, which was found to be equal to that of indomethacin, a well-known anti-inflammatory agent, without inducing any apparent acute toxicity or gastric damage.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Through bioassay-guided fractionation procedures three flavonoids, 3-O-methylquercetin (1), 3,7-O-dimethylquercetin (2) and 3,7-O-dimethylkaempferol (3), were isolated as the potent antinociceptive and anti-inflammatory principles. Although 1 was previously reported to possess in vivo anti-inflammatory activity (Wei et al, 2001), this is the first report on the in vivo antiinflammatory and antinociceptive effects of other flavonoids 2 and 3. A remarkable point might be the potency of these flavonoids, which was found to be equal to that of indomethacin, a well-known anti-inflammatory agent, without inducing any apparent acute toxicity or gastric damage.…”
Section: Resultsmentioning
confidence: 93%
“…It should be noted that 3,7-O-dimethylquercetin (2) was isolated as one of the active anti-inflammatory and antinociceptive principles of the leaves in the present study. Wei et al (2001) revealed that 3-O-methylquercetin (1) (also known as isorhamnetin) as the active anti-inflammatory principle of Rhamnus species and it is suggested that a possible activity mechanism is through inhibition of histamine release from peritoneal mast cells, as well as the release of ␤-glucuronidase and lysozyme from and superoxide anion formation from rat neutrophils. 3-O-methylquercetin (1) was also reported to inhibit the development of cotton-pellet-induced granuloma in mice (Pelzer et al, 1998) and in vitro xanthine oxidase inhibitory activity (Cimanga et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The degranulation of mast cells and neutrophils and the activation of macrophages and microglial cells contribute to inflammatory disorders. The compound inhibited the release of histamine from peritoneal mast cells, the release of ␤-glucuronidase and lysozyme from rat neutrophils and superoxide anion formation from rat neutrophils (Wei et al, 2001), and exhibited xanthine oxidase inhibitory and superoxide scavenging activities (Cimanga et al, 2001). It also inhibited carrageenan-induced mouse paw edema, and both 1 and genkwanin (3) were reported to inhibit the development of cotton-pellet-induced granuloma in mice (Pelzer et al, 1998).…”
Section: Discussionmentioning
confidence: 95%
“…Although quercetin, in general, has been reported to be anti-inflammatory (34), previous studies (26,39) have shown that quercetin exerts significant modulatory effects on gene expression as well as protein synthesis of both pro-and antiinflammatory molecules. A previous study (26) showed that quercetin up-regulated the Th-1-derived proinflammatory cytokine gamma interferon, while it reciprocally inhibited the Th-2-derived anti-inflammatory cytokine interleukin-4.…”
Section: Discussionmentioning
confidence: 99%